The 60/30/10 Rule of Marketing for Prosthodontists - Kirk Behrendt, ACT Speaker & Coach (Journal of Prosthodontics, 2006)
One of the questions we get frequently is, “Where should we spend our resources in marketing?’’ The answer is. . .it depends on how well you and your practice have evolved